Electrochemical Impedance Spectroscopy as an Analytical Tool for the Prediction of the Dynamic Charge Acceptance of Lead-Acid Batteries - Bauknecht, Sophia; Kowal, Julia; Bozkaya, Begüm; Settelein, Jochen; Karden, Eckhard (Batteries (Basel), 2022)
The subject of this study is test cells extracted from industrially manufactured automotive batteries. Each test cell either had a full set of plates or a reduced, negative-limited set of plates. With these test cells the predictability of the dynamic charge acceptance (DCA) by using electrochemical impedance spectroscopy (EIS) is investigated. Thereby, the DCA was performed according to EN 50342-6:2015 standard. The micro cycling approach was used for the EIS measurements to disregard any influencing factors from previous usage. During the evaluation, Kramers-Kronig (K-K) was used to avoid systematic errors caused by violations of the stationarity, time-invariance or linearity. Furthermore, the analysis of the distribution of relaxation times (DRT) was used to identify a usable equivalent circuit model (ECM) and starting values for the parameter prediction. For all cell types and layouts, the resistance R1, the parameter indicating the size of the first/high-frequency semicircle, is smaller for cells with higher DCA. According to the literature, this semicircle represents the charge transfer reaction, thus confirming that current-enhancing additives may decrease the pore diameter of the negative electrode.